Phylogenetic structure of communities between temperate and tropical regions: Exploring patterns through literature datasets - Araujo Martins, Clarissa; Silveira, Maurício; Saito, Victor S.; Costa-Pereira, Raul [UNESP]; Moreira Sugai, Larissa Sayuri [UNESP]; Pays, Olivier; de Oliveira Roque, Fabio (Elsevier, 2018)
Latitudinal patterns of diversity are one of the most striking large-scale biological phenomena and several hypotheses have been proposed to explain them. Using data from literature-surveys we investigated how phylogenetic patterns in microorganisms, plants, and, metazoans communities differ between the tropical and temperate regions and then explored possible ecological and evolutionary process that could shape such patterns. Using the Net Relatedness Index, we analyzed data from 1486 biological communities, collected in 32 articles that considered the phylogenetic structure of biological communities. We found a pattern of phylogenetic clustering in both regions for microorganisms, while for plants we found phylogenetic clustering in temperate regions and phylogenetic overdispersion in the tropics. We did not detect a clear pattern of clustering or overdispersion in tropical or temperate regions in metazoans. From these patterns we explore different ecological and evolutionary processes that have shaped these communities over space and time.
Keywords: Metazoans; Microorganisms; Phylogenetic clustering; Phylogenetic overdispersion; Plants; Tropical and temperate regions